Soluble Epoxide Hydrolase Inhibition for Ocular Diseases: Vision for the Future - Park, Bomina; Corson, Timothy W. (Frontiers in Pharmacology, 2019)
Ocular diseases cause visual impairment and blindness, imposing a devastating impact on quality of life and a substantial societal economic burden. Many such diseases lack universally effective pharmacotherapies. Therefore, understanding the mediators involved in their pathophysiology is necessary for the development of therapeutic strategies. To this end, the hydrolase activity of soluble epoxide hydrolase (sEH) has been explored in the context of several eye diseases, due to its implications in vascular diseases through metabolism of bioactive epoxygenated fatty acids. In this mini-review, we discuss the mounting evidence associating sEH with ocular diseases and its therapeutic value as a target. Substantial data link sEH with the retinal and choroidal neovascularization underlying diseases such as wet age-related macular degeneration, retinopathy of prematurity, and proliferative diabetic retinopathy, although some conflicting results pose challenges for the synthesis of a common mechanism. sEH also shows therapeutic relevance in non-proliferative diabetic retinopathy and diabetic keratopathy, and sEH inhibition has been tested in a uveitis model. Various approaches have been implemented to assess sEH function in the eye, including expression analyses, genetic manipulation, pharmacological targeting of sEH, and modulation of certain lipid metabolites that are upstream and downstream of sEH. On balance, sEH inhibition shows considerable promise for treating multiple eye diseases. The possibility of local delivery of inhibitors makes the eye an appealing target for future sEH drug development initiatives.